Internship at City Centrepoint Sdn Bhd / Nurain Afiqah Ramli - Ramli, Nurain Afiqah (Universiti Teknologi MARA, Perlis, 2024)
During my enriching and memorable 6-month industrial training at City Centrepoint Sdn. Bhd. I, Nurain Afiqah, a Human Resources student, am sincerely grateful for the valuable opportunity to intern at this distinguished establishment. City Centrepoint Sdn Bhd, envisioned as an international hub by day and a lifestyle haven by night, boasts diverse components such as corporate towers, cyber office suites, serviced residences, hotels, leisure attractions, a data centre, and a 1.5 million sq ft super-regional shopping mall. Throughout this internship, I have refined my skills in payroll management, training provider processes, administration, and project handling. Under the guidance of Ellie, Tan Pei Li, and Iris, I have actively contributed to the company's objectives, gaining valuable insights into the payroll department and administration. The SWOT and PESTEL analysis of i-City provides crucial insights into its current position and the external operating environment. i-City's strengths lie in its robust procedures and policies, emphasizing the priority of Standard Operating Procedures (SOP) and the establishment as a One-Stop Entertainment Center. However, weaknesses include a very rigid policy regarding ticket refunds and customer service challenges at i-City Theme Park. On a positive note, there are opportunities to create new attractions with prominent cartoon characters and to offer employment opportunities to senior citizens and persons with disabilities (OKU). Meanwhile, threats include environmental factors like weather conditions and leasing-tenant affairs. This internship has afforded me a comprehensive understanding of i-City's internal operations and the external challenges it faces. In conclusion, my internship at i-City has been a transformative experience, providing profound insights into the dynamic sector. The SWOT analysis serves as a strategic guide for future endeavors, underscoring the importance of continuous improvement and adaptation to industry trends.